Harald Szeemann museum of obsessions - Phillips, Glenn 1974-; Kaiser, Philipp 1972-; Chon, Doris; Rigolo, Pietro 1981- (Getty Research Institute, 2018)
"An examination of the career of the influential Swiss curator Harald Szeemann (1933-2005), drawing on his extensive archive and library housed at the Getty Research Institute, Los Angeles"...Provided by publisher